Nucleoporin 93 mediates β-catenin nuclear import to promote hepatocellular carcinoma progression and metastasis. (1st February 2022) - Lin, Cen-Shan; Liang, Yuyi; Su, Shu-Guang; Zheng, Yin-Li; Yang, Xia; Jiang, Neng; Fu, Lingyi; Zhou, Jing; Zhang, Ying; Deng, Ru; Wang, Chun-Hua; Lu, Shi-Xun; et al.
Abstract: Nuclear pore complex (NPC) embedded in the nuclear envelope, is the only channel for macromolecule nucleocytoplasmic transportation and has important biological functions. However, the deregulation of specific nucleoporins (Nups) and NPC–Nup-based mechanisms and their function in tumour progression remain poorly understood. Here, we aimed to identify the Nups that contribute to HCC progression and metastasis in 729 primary hepatocellular carcinoma (HCC) cases using molecular, cytological, and biochemical techniques. Our results revealed elevated Nup93 expression in HCC tissues, especially in cases with metastasis, and was linked to worse prognosis. Furthermore, Nup93 knockdown suppressed HCC cell metastasis and proliferation, while Nup93 overexpression promoted these activities. We observed that Nup93 promotes HCC metastasis and proliferation by regulating β-catenin translocation. In addition, we found that Nup93 interacted with β-catenin directly, independent of importin. Furthermore, LEF1 and β-catenin facilitated the Nup93-mediated metastasis and proliferation in HCC via a positive feedback loop. Thus, our findings provide novel insights into the mechanisms underlying the Nup93-induced promotion of HCC metastasis and suggest potential therapeutic targets in the LEF1–Nup93–β-catenin pathway for HCC therapeutics. Highlights: Nucleoporins is dysregulated in hepatocellular carcinoma. Nup93 contributes to HCC progression and metastasis and indicates poorer prognosis. Nup93 regulates β-catenin nuclear import. Nup93 increases phosphorylation of β-catenin. β-catenin in the nucleus activates Nup93 transcription by binding to transfactor LEF1.